Didactical Process Analysis (DPA) - Stukát, Karl Gustav (University of Gothenburg, 2016)
The DPA-project aimed to identify main structures in the teaching process, and to study the relationships between process variables and product variables. The following types of variables were included: 1) Environmental variables, 2) Teacher characteristics, 3) Pupil characteristics, 4) The teaching process, and 5) Teaching products (cognitive and non-cognitive pupil changes). The study was conducted using a predetermined observation diagram for identifying different behaviour categories.

The project included 80 teachers, one for each school class, and their pupils from schools in Gothenburg and its neighbouring municipalities. Among the 80 classes, 60 were regular classes and 20 classes were remedial classes. For the collection of process data, 10 lessons divided over five different subjects for each class were video as well as audio recorded. The collection of other data involved questionnaires, tests measuring aptitudes, attitudes and personality, and public records of school size, grades in 3rd grade and the teachers’ age, year of service and ratings.

The lessons were documented through time-sampled video supplemented by continuous audio recordings. Each teacher was recorded for about 120 minutes, corresponding to 10-12 minutes per lesson. Altogether, there are around 150 hours of video recordings and 600 hours of audio recordings. The video recording was filmed with two video cameras in the classroom; one with wide angle towards the class, and one remote moving camera that followed the teacher. Audio was recorded with a fixed microphone mounted in the ceiling as well as a wireless microphone borne by the teacher. The idea was that the recording devices to a minimum extent would affect the natural course of events in the class room.

DPA offers a unique collection of material that provides possibilities to study socialisation processes, learning, teaching, and a number of other phenomena from a historical and comparative perspective. The target group for the database is primarily researchers within the educational research domain, but this sort of video and audio recordings are also suitable for research in other fields and disciplines such as sociology, linguistics, and history.

Purpose:

The objectives of the DPA project can be formulated in the following points: 1) to identify the main structures in the teaching process, 2) to study the relation between condition variables and the teaching process, 3) to study correlations between process and product variables, 4) to study correlations between teacher characteristics, pupil characteristics, and teaching effects, 5) to compare process structures in different school subjects, and 6) to compare process structures in different school environments (e.g. regular classes and remedial classes).

The material consists of video and audio files; Audio, uncompressed, wav format (1.23 TB); Audio, compressed, MP3 format (71.4 GB); Video, uncompressed, mov format (1.81 TB); Video, compressed, MP4 format (123 GB).

In order video and audio are delivered in compressed format (total 194 GB), together with the documentation. Uncompressed files can be delivered on demand .

DPA-projektet syftade till att kartlägga huvudstrukturer i undervisningsprocessen och att studera relationer mellan processvariabler och produktvariabler. Följande variabelgrupper ingick: 1) Miljövariabler, 2) Lärarkarakteristika, 3) Elevkarakteristika, 4) Undervisningsprocessen, 5) Undervisningsprodukter (kognitiva och icke-kognitiva elevförändringar). Studien genomfördes med hjälp av ett på förhand bestämt observationsschema som klassificerade olika beteendekategorier.

I projektet ingick 80 lärare, en för varje skolklass, och deras elever från skolor i Göteborgsområdet. Av de 80 klasserna var 60 vanliga klasser och 20 var hjälpklasser. För insamlingen av processdata video- och ljudinspelades 10 lektioner vardera för varje klass, fördelat över fem olika ämnen. Insamlingen av övriga data bestod av frågeformulär, begåvnings-, attityd- och personlighetstest och registerutdrag om bland annat skolans storlek, betyg i årskurs 3 och lärarnas ålder, tjänsteår och betyg.

Lektionerna dokumenterades genom tidssamplad video kompletterat med kontinuerliga ljudinspelningar. Varje lärare spelades in i cirka 120 minuter, motsvarande 10-12 minuter per lektion. Totalt finns cirka 150 timmar video- och 600 timmar ljudinspelningar. De rörliga bilderna spelades in med två videokameror i klassrummet; en med vidvinkel mot klassen och en fjärrstyrd och rörlig kamera som följde läraren. Ljud spelades in med en fast mikrofon monterad i taket samt en trådlös buren av läraren. Idén var att inspelningsutrustningen i minsta möjliga utsträckning skulle påverka det naturliga skeendet i klassrummet.

DPA erbjuder en unik samling material som ger möjligheter att studera socialiseringsprocesser, lärande, undervisning och en rad andra fenomen från ett historiskt och komparativt perspektiv. Målgruppen för databasen är i första hand forskare inom utbildningsvetenskap, men video- och ljudinspelningar av denna typ lämpar sig också för forskning relaterad till andra områden och discipliner såsom sociologi, språkvetenskap och historia.

Syfte:

DPA-projektets syften kan formuleras i följande punkter: 1) att kartlägga huvudstrukturer i undervisningsprocessen, 2) att studera samband mellan förutsättningsvariabler och undervisningsprocessen, 3) att studera samband mellan process- och produktvariabler, 4) att studera samband mellan lärar- och elevegenskaper och undervisningseffekter, 5) att jämföra processtrukturer i olika skolämnen och 6) att jämföra processtrukturer i olika skolmiljöer (t ex vanlig klass och hjälpklass).

Materialet består av video- och ljudfiler; Ljud, okomprimerat, i wav-format (1,23 TB); Ljud, komprimerat, i mp3-format (71,4 GB); Video, okomprimerat, i mov-format (1,81 TB); Video, komprimerat, mp4-format (123 GB).

Vid beställning levereras video och ljud i komprimerat format (totalt 194 GB) tillsammans med tillhörande dokumentation. Vid efterfrågan kan okomprimerade filer lämnas.
Didaktisk processanalys (DPA)
Keywords: educational environment; utbildningsmiljö; schoolteachers; skollärare; teacher role; lärarroll; schoolchildren; skolbarn; school-student relationship; skola-elevförhållande; student behaviour; elevbeteende; school time; skoltid; educational research; utbildningsforskning; special education teachers; speciallärare; socialization; socialisation; EDUCATION; UTBILDNING; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Educational Sciences; Utbildningsvetenskap; Didactics; Didaktik